1995
DOI: 10.1002/ijch.199500013
|View full text |Cite
|
Sign up to set email alerts
|

Soft Matter in a Tight Spot: Nanorheology of Confined Liquids and Block Copolymers

Abstract: The linear frequency‐dependent shear rheology and force–distance profiles of molecularly‐thin fluids of very different structure were contrasted: a globular molecule octamethylcyclotetrasiloxane (OMCTS), branched alkanes (3‐methylundecane and squalane), and a polymer brush in near‐theta solution (polystyrene‐polyvinylpyridine). In each case the data suggest a prolongation of the longest relaxation time (τ1) with increasing compression. At frequencies ω > 1/τ1 the shear response was “solid‐like”, but at ω < 1/τ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
91
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 45 publications
13
91
3
Order By: Relevance
“…The same appears to be true for squalane as shown in figure 7(c). This observation further validates the measurements of Granick et al [33] (using SFA) and lately by Lim and O'Shea [34] (using AFM), showing oscillatory forces exist for branched molecules such as squalane and 3-methylundecane (C12H26).…”
Section: Resultssupporting
confidence: 91%
“…The same appears to be true for squalane as shown in figure 7(c). This observation further validates the measurements of Granick et al [33] (using SFA) and lately by Lim and O'Shea [34] (using AFM), showing oscillatory forces exist for branched molecules such as squalane and 3-methylundecane (C12H26).…”
Section: Resultssupporting
confidence: 91%
“…However, recent computer simulations of octane and isooctane did not reveal this unexpected difference in the solvation force profiles [23]. Also recent experiments of 3-methylundecane show that the solvation force show still an oscillatory behaviour, however the amplitudes of the oscillations are smaller than for linear undecane [24]. A similar decrease in the amplitudes of the oscillations has been found in recent computer simulations of n-hexadecane and squalane [25].…”
Section: Introductionmentioning
confidence: 59%
“…[2][3][4]56 It is generally observed that the properties of thin films go from liquidlike at large film thicknesses and low pressures toward more solidlike at higher confinement. [2][3][4]56 Results Force-Distance Measurements. Static interaction forces (normalized by the mean radius of curvature of the undeformed solid surfaces, R) are plotted against film thickness in Figure 1.…”
Section: Methodsmentioning
confidence: 99%